Caracterización hidrológica de la subcuenca del río Quirimán, en el cantón de Nicoya - Martínez-Ramírez, Carlos Humberto (Instituto Tecnológico de Costa Rica, 2018)
The canton of Nicoya, located in the province of Guanacaste, lacks an updated regulatory plan. Currently, it is subject to a document of the year 1983. It is for this reason that it is necessary to develop studies in the hydrographic basins of Nicoya that serve as the basis for the elaboration of a new plan. Given this situation, a hydrological characterization of the sub-basin of the Quirimán River was developed to help solve this problem. First, it was characterized morphologically sub-basin of the Quirimán River using free-use programs to analyze the physiology of the study area. It was determined that the basin has an area of 160 km2 characterized as large, classified as exorheic that drains the Nosara River, whose erosive capacity is high and which has a moderate to good drainage. Land use and capacity maps were prepared, which allowed creating a map of land use conflicts, identifying an overuse of use in the aquifer recharge areas located in the upper part of the basin and a high capacity for the development of land use. agricultural crops in the middle and lower parts of the basin. Afterwards, the water potential of the Quirimán River was determined from flows measured in gauges made by the Water Directorate and the water balances for a period of 10 years. The Quirimán River can help guarantee the demand for human consumption of water for the district of Nicoya until the year 2025, and generate economic resources of 17 million colones. Becoming a source of employment and economic and social development. These economic resources can be invested including for the development of studies and environmental programs in the basin.
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018
Keywords: Uso del suelo; Capacidad; Cuencas; Drenaje; Erosión